Effects of a Low Dose of Orally Administered Creatine Monohydrate on Post-Fatigue Muscle Power in Young Soccer Players - Jofre-Saldia, E (2024)
The use of creatine monohydrate (Cr) in professional soccer is widely documented. However, the effect of low doses of Cr on the physical performance of young soccer players is unknown. This study determined the effect of a low dose of orally administered Cr on muscle power after acute intra-session fatigue in young soccer players. Twenty-eight young soccer players (mean age = 17.1 +/- 0.9 years) were randomly assigned to either a Cr (n = 14, 0.3 g.kg(-1).day(-1) for 14 days) or placebo group (n = 14), using a two-group matched, double-blind, placebo-controlled design. Before and after supplementation, participants performed 21 repetitions of 30 m (fatigue induction), and then, to measure muscle power, they performed four repetitions in half back squat (HBS) at 65% of 1RM. Statistical analysis included a two-factor ANOVA (p < 0.05). Bar velocity at HBS, time: p = 0.0006, eta(2)(p) = 0.22; group: p = 0.0431, eta(2)(p) = 0.12, time x group p = 0.0744, eta(2)(p) = 0.02. Power at HBS, time: p = 0.0006, eta(2)(p) = 0.12; group: p = 0.16, eta(2)(p) = 0.06, time x group: p = 0.17, eta(2)(p) = 0.009. At the end of the study, it was found that, after the induction of acute intra-session fatigue, a low dose of Cr administered orally increases muscle power in young soccer players.